From Collective Use Value to Spatial Commodification: The Transformation of Waqf in Turkish Urban Development - Dogan Delil Gültekin; Darnilawati Darnilawati (MD Research Center Yogyakarta, 2026)
The tension between urban capitalism and Islamic philanthropy in Turkey has marginalized waqf as a historical urban development institution. This study aims to analyze waqf’s transformation and recontextualization within modern Turkish urban development, focusing on institutional dynamics, social distribution, and cultural-religious value shifts. Employing a qualitative thematic literature review of 46 peer-reviewed sources, this research integrates Lefebvre’s production of space theory, urban political economy, and institutional theory. The findings reveal four transformative patterns: institutional shift from decentralized community governance to state control; waqf’s dual role in reducing and potentially reinforcing inequality; value transformation from religious devotion toward strategic philanthropy; and spatial commodification prioritizing exchange over use value. Waqf has fundamentally shifted from collective utility toward commodification, with institutional, market, and state forces reducing its social function while inequality in asset distribution persists. This study argues that revitalizing waqf requires integrating religious values, institutional innovation, and inclusive urban policies. The research contributes theoretical synthesis linking waqf studies with critical urban theory and identifies pathways for legal and planning reforms.